2019
DOI: 10.5505/yeditepe.2019.70288
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous glands within odontogenic cysts

Abstract: Aim: Sebaceous glands are rarely observed in odontogenic cysts whereas these structures are the histopathologic features of dermoid cysts. Dermoid cyst growth is slow and its biologic behaviour is silent; after the cyst is removed, recurrence is not observed. However, there are some developmental odontogenic cysts that have a local aggressive course and high levels of recurrence and sebaceous glands may present in these types of cyst. The aim of the study is to evaluate the histopathologic and clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…A recent study, regarding the bone loss in peri-implantitis, has demonstrated that this process can be the consequence of an oxidative stress and treating peri-implantitis with antioxidant herbal extract therapy can be a good choice [38].…”
Section: Blockmentioning
confidence: 99%
“…A recent study, regarding the bone loss in peri-implantitis, has demonstrated that this process can be the consequence of an oxidative stress and treating peri-implantitis with antioxidant herbal extract therapy can be a good choice [38].…”
Section: Blockmentioning
confidence: 99%